Time-Dependent Solution And Optimal Control Of A Bulk Service Queue - Selim, S.Z. (2020)
We consider the queueing system denoted by M/M(N)/1/N where customers are served in batches of maximum size N. The model is motivated by a traffic application. The time-dependent probability distribution for the number of customers in the system is obtained in closed form. The solution is used to predict the optimal service rates during a finite time horizon.